PENINGKATAN KEMAMPUAN BERKOMUNIKASI DENGAN MEDIA PAPIN (PAPAN PINTAR) PADA SISWA KELAS V - Kamala Asrih Sastri; Joni Bungai; Carolina Fransiska (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This research is based on the low communication skills of students in Indonesian learning, especially in the material "Unique and Interesting Events". This research aims to improve the communication skills of grade V (five) students of SD Negeri 3 Pahandut through the use of PAPIN (Smart Board) media in Indonesian learning material "Unique and Interesting Events". The background of this research is the low communication skills of students, both verbally and in writing, as well as the lack of use of varied and interesting learning media. This research is a Class Action Research (PTK) with the Kemmis and McTaggart models which is carried out in two cycles. The subjects in this study were 22 students of class V (five) of SD Negeri 3 Pahandut. The data collection technique uses observation, tests, and documentation, which are analyzed descriptively quantitatively. The results of this study show that the use of PAPIN media can improve students' communication skills. The average score of students' communication skills increased from 49.18 in pre-action, to 58 in cycle I, and reached 76.6 in cycle II. In addition, students' learning activities also increased from the category of being quite active in cycle I to being very active in cycle II. This improvement shows that PAPIN media is effective in creating an active, fun learning atmosphere, opinions, and orally. Thus, the use of PAPIN media can be used as an alternative learning strategy to improve the skills of students in elementary school, especially in Indonesian lessons.